Angiotensin‐converting enzyme inhibitor/angiotensin II receptor blocker treatment and haemodynamic factors are associated with increased cardiac mRNA expression of angiotensin‐converting enzyme 2 in patients with cardiovascular disease. (20th October 2020) - Lebek, Simon; Tafelmeier, Maria; Messmann, Rebecca; Provaznik, Zdenek; Schmid, Christof; Maier, Lars S.; Birner, Christoph; Arzt, Michael; Wagner, Stefan
Abstract: Aims: Coronavirus disease 2019 (COVID‐19) is a widespread pandemic with an increased morbidity and mortality, especially for patients with cardiovascular diseases. Angiotensin‐converting enzyme 2 (ACE2) has been identified as necessary cell entry point for SARS‐CoV‐2. Previous animal studies have demonstrated an increased ACE2 expression following treatment with either angiotensin‐converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB) that have led to a massive precariousness regarding the optimal cardiovascular therapy during this pandemic. Methods and results: We have measured ACE2 mRNA expression using real‐time quantitative polymerase chain reaction in atrial biopsies of 81 patients undergoing coronary artery bypass grafting and we compared 62 patients that received ACEi/ARB vs. 19 patients that were not ACEi/ARB‐treated. We found atrial ACE2 mRNA expression to be significantly increased in patients treated with an ACEi or an ARB, independent of potential confounding comorbidities. Interestingly, the cardiac ACE2 mRNA expression correlated significantly with the expression in white blood cells of 22 patients encouraging further evaluation if the latter may be used as a surrogate for the former. Similarly, analysis of 18 ventricular biopsies revealed a significant and independent increase in ACE2 mRNA expression in patients with end‐stage heart failure that were treated with ACEi/ARB. On the other hand, cardiac unloading with a left ventricular assist device significantly reduced ventricular ACE2 mRNA expression. Conclusion: Treatment with ACEi/ARB is independently associated with an increased myocardial ACE2 mRNA expression in patients with coronary artery disease and in patients with end‐stage heart failure. Further trials are needed to test whether this association is deleterious for patients with COVID‐19, or possibly protective. Nevertheless, haemodynamic factors seem to be equally important for regulation of cardiac ACE2 mRNA expression. Abstract : Treatment with angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers increases independently myocardial mRNA expression of the SARS‐CoV‐2 cell entry point ACE2 in high‐risk patients.